CORROSION STUDIES ON SS-321 IN CHLORIC-ACID SOLUTION MEDIUM - Nurdin Effendi; Aziz K. Jahja (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
CORROSION STUDIES ON SS-321 IN CHLORIC-ACID SOLUTION MEDIUM. Experimental corrosion studies on commercial AISI-321 have been carried out. The experiments were carried out in a chloric- acid medium with a concentration variation of 0.1 mol. 0.2 mol.. 0.3 mol. and 0.4 mol corresponding to pH values of 1.0, 0.7, 0.523, and 0.4 respectively. The experiments were carried out using a type M-273 EG&G potentiostat/galvanometer test instrument. The post-corrosion samples’ microstructure were analyzed with the aid of EDS (energy dispersive spectroscopy) equipped SEM instrument to detect the presence of any viable corrosion byproducts. For further verification. X-ray diffraction method was also used to detect any possible emerging corrosion byproducts on the samples’ surfaces. Experimental results confirm that AISI-321 commercial alloys immersed in a chloric acid corrosion medium with a variation of concentration experience very little or almost no corrosion, and that according to the so-called Fontana’s criteria these test-materials turn out to have an excellent resistance toward chloric acid corrosion. This is also evidenced by the very low corrosion rate value measured in this study. EDS study and X-ray diffraction results indicate that the possible ensuing corrosion byproducts are iron oxides, chrome oxides, and iron chlorides.